Parametars for the evaluation of the quality of PVC containers for pharmaceutical preparations - Aneta Dimitrovska; Liljana Ugrinova; Suzana Trajkovic-Jolevska; Slavica Tanceva (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2002)
An overview of the parameters for the evaluation of the quality of poly(vinyl chloride) (PVC) containers for pharmaceutical preparations is made. The requirements for the quality of PVC containers regulated by Ph. Eur., DIN and ISO standards differ in the prescribed parameters for physical, chemical and biological examination. Different ranges of tolerance for certain parameters also exist. The comparison of the parameters prescribed for these types of containers in Ph. Eur., DIN and ISO standards is made for a more detailed evaluation of PVC container quality